Estimation of leg power: A two-variable model - Shetty, A. B. (Sports Biomechanics, 2002)
Leg power is an essential component for success in sports and athletic performance. Therefore, the leg power measurement may help athletes, coaches, athletic trainers, and rehabilitation specialists in selecting, treating, and training athletes for a specific sport. Nineteen untrained male subjects performed 'jump and reach' vertical jumps on a force platform. Power values were calculated from the force versus time data obtained from the force platform. A regression equation was obtained to predict the power values using the weight of an individual and the 'jump and reach' height as independent variables. The regression equation is given by p = -666.3+14.74 [Mass (kg)] +1925.72 [Height (m)]; [R-square = 0.69, p < 0.05].